DIGITAL PLAYGROUND: FRIEND OR FOE TO THE CHILDREN? - Krstić, Nataša (The European Journal of Applied Economics, 2021)
For the central entertainment industry of the 21st century - online gaming, children are undoubtedly the key consumer group. Although research on the impact of the gaming industry on children mainly deals with negative effects such as addiction, violent content, inappropriate conduct and monetization of personal data, there are also many positive effects – family fun, virtual socializing, improving cognitive skills and using games as a teaching tool. Therefore, the task of all participants in the gaming industry value chain is to maximize the positive and minimize the negative impacts on children. A survey conducted among 893 young gamers in Serbia exposed their habits in consuming online games and indicated whether their rights are protected during the gameplay. The conclusion provides recommendations for key stakeholders in the gaming industry's ecosystem on how to make the digital playground inclusive, safe and responsible when it comes to respecting children's rights.
Keywords: child rights; Serbia; gaming; gaming industry; COVID-19